Unleashing the power of digital signage : content strategies for the 5th screen - Kelsen, Keith (Focal Press, 2010)
Implement a successful content strategy that optimizes the return-on-message performance of your digital signage program. Learn the message attributes for each of the three core network types (Point of Wait, Point of Sale, and Point of Transit), how to measure the program's effectiveness and strike a balance that uses messages effectively alongside the other advertising campaign elements. Through the included interviews, gain access to the wisdom of more than 45 experts, each of whom has deployed and operated successful digital signage networks. The companion website, www.5thscreen.info, features real-world implementations and video blog programming that includes interviews with industry notables. You'll learn how to: create a strategic communications blueprint and style guide for your network keep content flowing automatically-and therefore remaining relevant use data on viewers and traffic to build a programming schedule legally acquire and repurpose content more accurately predict where the future of content will lead Foreword by Joe Pine and Jim Gilmore authors of "The Experience Economy" and "Authenticity" Develop a strategy and methodology for creating cross platform content including mobile. Employ a return on message control that measures 7 key index factors to optimize digital signage results. Leverage existing traditional assets, TV PC, print and mobile to create powerful content for digital signage. Use real-world creative content deployments featured on the companion Web site to inform your own work.